Analysis of organochlorine pesticides in plain milk using direct injection on an ISRP column, with column switching - Menezes, M. L.; Felix, G. (Marcel Dekker Inc, 1996)
A simple and rapid procedure for extraction and separation from aldrin, DDT, endrin, heptachloro- and methoxychloro-organochlorine pesticides in raw milk has been developed by direct injection into an HPLC system without pretreatment of the samples, using an ISRP column.